Zakat performance: the role of management decision in spiritual servant government commitment / Bedjo Santoso, Marno Nugroho and Leonova Olga Viktorovna - Santoso, Bedjo; Nugroho, Marno; Viktorovna, Leonova Olga (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2024)
This study offers a new concept of Spiritual Servant Government Commitment synthesizing from government role, trust, and spiritual theory combined with the social identity concept for addressing the issues that arose and covered the research gap. This study involved 400 respondents throughout Indonesia including Muslim academicians, BAZNAS (Government Zakat Agency), and Islamic scholars. The research identified five variables influencing Zakat performance: SSGC, ICT capability and GCG elements including transparency, accountability, and credibility. Effective management decisions in implementing and promoting SSGC is crucial for strengthening Zakat performance and, ultimately, enhancing the welfare of society. The finding revealed that GCG elements did not directly affect Zakat performance but was be mediated by SSGC. Transparency, accountability, and credibility significantly affected SSGC, and subsequently SSGC affected Zakat Performance. SSGC strengthened Zakat performance through proactive involvement of government based on religious commitment values in providing regulations and infrastructures, ultimately increasing the welfare of society, highlighting the significance of management decisions in fostering spiritual values within the governance framework. This study introduced SSGC as a new concept in the role of leadership in government theory, by incorporating prophetic servant leadership in Zakat management. This research fulfills theoretical gaps and offers new perspectives on spiritual-religious values, addressing the relationship between variables and contributing to the development of a new concept which strengthened the theories involved,